Psychosocial Factors Driving Entrepreneurial Intention among High School Students in Conflict-Affected Southern Provinces of Thailand - Densumite, Sorfina; Dureh, Nurin; Laipaporn, Jetsada (The Journal of Behavioral Science, 2025)
Background/ problem: The three border provinces in the deep south of Thailand face economic problems and insurgency, hindering youth development. Promoting entrepreneurship through entrepreneurial intention among high school students could support economic growth and strengthen long-term regional resilience. Objective/ purpose: This study aimed to examine the psychosocial determinants influencing entrepreneurial intention among final-year high school students in Islamic private schools as the dominant educational institutions in this region. Design and Methodology: This quantitative study employed stratified random sampling to collect data from 2,078 final-year high school students enrolled in the Islamic private schools in the investigated area. The data was analyzed using structural equation modelling. Results: The findings confirm that entrepreneurial intention was positively and significantly influenced by personal attitude (b = .90, p = .00), risk-taking (b = .18, p = .00), and financial behavior (b = .04, p = .02), while entrepreneurial education (b = .33, p = .00), subjective norms (b = .19, p = .00), perceived behavioral control (b = .10, p = .00), individual-level unrest impact (b = .03, p = .02) and societal-level unrest impact (b = –.10, p = .00) significantly impacted entrepreneurial intentions through personal attitudes. Conclusion and Implications: This study identifies personal attitude as a key driver of entrepreneurship among high school students and highlights extended factors, unrest impacts, entrepreneurial education, financial behavior, and risk-taking, as critical additions to the theory of planned behavior in conflict-affected contexts. Public policy should address these factors to foster youth entrepreneurship and support sustainable development.